From Decolonising Sexual Violence Discourse to Investigating Primate Coexistence: A Discussion with Louise du Toit - Du Toit, Louise; Joubert, Paul (The Stellenbosch Socratic Journal, 2025)
In 2021, Louise du Toit became the first woman in the Department of Philosophy at Stellenbosch University to be promoted to full professor, giving her inaugural lecture in August 2025. In this interview, Paul Joubert asks Du Toit to recount her intellectual journey to this point, reflecting on the gendered dynamics of philosophy as a discipline, and the challenges of establishing an authoritative voice in a largely male-dominated field. The conversation explores Du Toit’s work on sexual violence, discussing the catalyst of her philosophical investigation into rape and the intersections of sexual violence with colonial–racist politics and with the struggle for decolonisation. Du Toit discusses the complex legacies of colonial constructions of Black sexuality, the challenges of addressing sexual violence without reproducing racist harms, and the institutional racism and misogyny that continue to shape the treatment of Black victims. The interview concludes with a discussion of her current projects, including her research on primate (human–baboon) co-existence.